Reconsider deschooling: Alternative towards more accessible and inclusive education - Agie Nugroho Soegiono; Aulia Anis; Saskia Rizqina Maulida (Masyarakat, Kebudayaan dan Politik, 2018)
This essay discusses deschooling concept as an alternative learning delivery method to achieve education for all. We argue that the deschooling idea, first introduced by Illich before the era of the Internet, has become relevant in relation to today’s education challenges. What we mean by deschooling in this paper is not the abolishment of the schooling system. Instead, the recall of deschooling discourse aims to provide more recognition of learning activities outside of the school setting. The learning webs, a key enabler in deschooling discourse, are realistic when implemented with the help of 21st century’s technology. The argument in this paper utilised an in-depth literature review and discourse analysis in the deschooling debate. To strengthen our argument, we have provided three case studies in the form of informal learning, non-formal learning and e-learning related to deschooling initiatives. Based on our findings, we can conclude that deschooling society is certainly viable. The principles used in deschooling, such as ﬂexibility, inclusiveness, adaptability and personalisation, are alternatives for everyone to have freedom of access, use, copy, and modify learning resources. We also found that there may be possible challenges, including the limitation of self-directed learning, the pitfall of institutionalised capital and a lack of social interaction.